Gluten-free cookies formulation using local composite flour of gadung, brown rice, and moringa leaves - Dayani, Fitri; Sari, Ratna Nurmalita (Journal of Agritechnology and Food Processing, 2023)
Fibre-rich snacks can be made from local ingredients that are abundant and gluten-free, such as gadung and moringa leaves. This study aims to determine the correct formulation in the production of cookies using a combination of local composite flour from gadung tubers, brown rice and moringa leaves. The parameters observed include organoleptic test, fibre content and physical properties of the cookies. This research was carried out using an experimental method with a fully randomised design with 4 treatments and 3 replicates. The composites used consisted of umbi gadung flour, brown rice flour and moringa leaf flour with the formulation 60 g: 30 g: 10 g (P1), 50 g: 20 g: 30 g (P2), 40 g: 40 g: 20 g (P3) and (3 g: 25 g: 40 g (P4). Based on the results of the data analysis using the SPPS programme, it is known that the composite formulation has a significant effect on the organoleptic and physico-chemical parameters of the cookies. The more moringa leaves are added, the lower the panelists' liking, the darker the colour of the biscuits and the more brittle the texture. In conclusion, P1 is the best composite formulation based on panelist preference with yellowish-brown cookie colour, low breakage and crude fibre content of 3.51%.